PENERAPAN METODE BREAK EVEN POINT DALAM PEMBIAYAAN MUDHARABAH DI BPRS HIK CILEUNYI - Indah Lestari Kusuma; Sofian Al-Hakim; Yusup Azazy (Al-Muamalat: Jurnal Ekonomi Syariah, 2020)
Harta Insan Karimah Islamic People's Financing Bank (BPRS) is a financial institution that applies the break even point method in an effort to prevent losses and make decisions in mudharabah financing. In its application, this method must be calculated carefully and thoroughly and know the magnitude of the benefits or its disadvantages and what if the calculations are wrong. Then the legal status is still being questioned. This study aims to determine the review of Islamic economic law on the application of the break-even point method in mudharabah financing at SRB HIK Parahyangan Cileunyi. The method used in this research is a descriptive case study. Based on the results of the study, it can be concluded that the application of the break-even point method cannot be made as a final decision because this method can only be used in a stable economic situation so as not to burden and cause injustice to. In a review of Islamic economic law, this method may be used because it is a business habit or 'urf that is known by business actors in the effort of risk loss management in stable economic conditions, this method is in accordance with the principles of muamalah namely principle' is or justice, principles antaradhin, the principle of manfaah (tabadu al-manafi '), the principle of ash-shiddiq and the principle of adam al-gharar and muamalah fiqh rules.